Data warehouse schema for monitoring key performance indicators (KPIs) for university teaching and learning using goal oriented approach - Abdullah, Mohammed Thajeel (2016)
The growth and development of universities, just as other organisations, depend on their abilities to strategically plan and implement development blueprints which are in line with their vision and mission statements. The actualizations of these statements –which are often abstracted into goals and sub-goals and linked to their respective actors –are better measured by defined key performance indicators (KPIs). And in universities that handle modestly large and heterogeneous data, development of data warehouse is important. Specifically, Universiti Utara Malaysia (UUM) is yet to have a data warehouse for monitoring its organisational KPIs. This study therefore proposes a data warehouse schema for university’s KPIs for teaching and learning KPIs using a Requirement Goal Analysis for Data Warehouse KPI(ReGADaK)approach which is an extension of goal-oriented requirement analysis and design (GRAnD). The proposed schema highlights the facts, dimensions, attributes and measures of UUM’s teaching and learning unit. The measures from the goal analysis of this unit serve as basis of developing the related university’s KPIs. The proposed data warehouse schema is evaluated through expert review, prototyping and usability evaluation. The findings from the evaluation processes suggest that the proposed data warehouse schema is suitable for university’s KPIs for teaching and learning KPIs monitoring and practicable.